Analisis Daya Dukung Lahan Permukiman Di Kota Manado - Tanie, Felisia Angel; Polii, Bobby Vian Jhon; Memah, Melsje Yellie (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the carrying capacity of residential land in Manado City by using the Building Coverage concept according to Muta'ali (2012) and based on the Regulation of the State Minister for Public Housing Number 11 of 2008 (PERMEN No.11 Tahun 2008). This research was conducted in Manado City North Sulawesi Province, which was carried out from March to May 2023. The types of data used in this research are primary data and secondary data. The data collection method was carried out using the Field Research Method, Institutional Survey and Literature Survey. The data analysis method used in this study is using two formulas, namely based on the Building Coverage concept and the Regulation of the State Minister for public Housing Number 11 of 2008 (PERMEN No. 11 Tahun 2008). The results of the study show that the carrying capacity of residential land in Manado City by using the Building Coverage concept (Liputan Bangunan) is 35%. This means that the availability of space in Manado City is generally good or there is still a lot of space that can be used for settlements. While sub-district that has the largest percentage of carrying capacity of residential land using the Building Coverage formula is Sario District at 94.81%, whereas the lowest percentage is in Mapanget District at 6.15%. The value of the Carrying Capacity of Residential Land (DDPm) in Manado citybased on the classification of the Regulation of the State Minister for Public Housing Number 11 of 2008 (PERMEN No. 11 Tahun 2008) is 10.51, which indicated that the DDPm value is > 1. This can be concluded that the carrying capacity of Residential land in Manado City is high and still able to accommodate people for living.